On-farm evaluation of elite sweet sorghum genotypes for grain and stover yields and fodder quality - Kumar, A.; Reddy, B.V.S.; Blümmel, Michael; Samireddypalle, A.; Ramana Reddy, Y.; Reddy, R.; Rao, P.S.; Reddy, P.S. (2010)
Sweet sorghum is a multipurpose crop that comes up well under rainfed conditions in semi-arid tropics. While the stalk juice from sweet sorghum used for ethanol production, its grain is used for food and the bagasse as animal feed. The investigation had four objectives: 1) to popularize sweet sorghum as food, feed and fuel crop; 2) to identify promising sweet sorghum cultivars under on-farm conditions for use as animal feed; 3) to study the associationships between cane yield and stalk sugar traits; and 4) to assess the options for utilizing stover and fresh/dried bagasse as livestock feed. Sweet sorghum cultivation is feasible and profitable under rainfed conditions in the study area with the hybrid CSH 22 SS. Results from on-farm evaluation of elite sweet sorghum hybrids and varieties and correlation studies indicated that dryland farmers gain from whole plant use of sweet sorghum as there is no significant tradeoff between grain yield and sugar/stover yields. The genetic enhancement of sweet sorghum is justifiable as the food and fodder value of the crop is not compromised by its improvement for bio-fuel value. The effective rumen degradable dry matter (ERDDM) for sweet sorghum bagasse (SSB) was 40.60 per cent and effective rumen degradable protein (ERDP) value was 55.30 per cent. The nutritive value of SSB in terms of the digestible crude protein (DCP) and total digestible nutrients (TDN) in sheep was 1.02, 50.67 per cent where as in buffaloes DCP was 0.98 and TDN 51.78 percent. Results from the limited on-farm animal experiments in milch buffaloes and sheep indicate that the potential of sweet sorghum stalks in the form of stover and bagasse in fresh or ensiled form as a source of roughage is good and further long term experiments are required to confirm the same.